Can an online scenario-based learning intervention influence preservice teachers’ self-efficacy, career intentions, and perceived fit with the profession? - Klassen, RM; Wang, H; Rushby, JV (Elsevier, 2023)
The purpose of this article is to explore how a brief, scalable, online scenario-based learning (SBL) intervention influences preservice teachers’ self-efficacy, career intentions, and perceived fit with the profession. A sample of 1,513 preservice teachers from a large undergraduate teacher education programme in Australia was recruited over two years to complete three SBL sessions (with four measurement points) over the course of three weeks. We conducted a series of latent change analyses to explore the patterns of change over time, with covariates including year in ITE programme, prospective teaching level, and sex. Results showed that self-efficacy, teaching commitment, and perceived fit with the profession increased after the initial SBL session, and the effect was maintained for self-efficacy and perceived fit, but not for teaching commitment. Implications for practice and further research are discussed.